Kinetics of the expressions of radiation-induced plasma proteins of the cardiac territory in electrophoresis - Celso V. Lima; Tarcisio P. R. Campos
ABSTRACT Introduction: Radiation induces acute and late alterations in blood proteins. Objective: The present study aims at analyzing in time kinetics the electrophoretic profiles of expression bands of blood protein, in the molecular weight range greater than and equal to that of albumin, modulated by ionizing radiation in the cardiac territory, in animal model. Material and methods: Animals were exposed to a whole-body dose of 5 Gy ionizing radiation (Co-60). Serum samples were collected from isogenic Wistar rats (control and irradiated groups). At a time kinetics of 12, 24, 48, 72, 96 hours and 35 days post-irradiation, thoracolaparotomies were performed with anesthesia, and 0.3 ml of blood was collected between the left ventricle and the pulmonary artery. The samples were held in heparin and their components were separated by centrifugation. Protein bands with similar molecular weight were identified by vertical 10% electrophoresis, silver staining. Results: The findings indicate a systemic acute altered expression of proteins with molecular weight greater than or equal to that of albumin in acrylamide gel, presenting suppression and increased expression due to modulation of preexisting bands, identified in time kinetics. Conclusion: These findings point out to acute alterations of protein expression modulated in time, but also to a late modulation of gene expression.